1989
DOI: 10.1007/bf00170851
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of synthetic racemic ptilocaulin: A novel cyclic guanidine

Abstract: (+)-Ptilocaulin, a novel cyclic guanidine extracted from the Caribbean sponge Ptilocaulis aff. P. Spiculifer, is reported to have broad spectrum antimicrobial activity in vitro as well as in vitro activity against L1210 murine leukemia. To more fully evaluate this compound as an anticancer agent, the in vitro cell growth inhibitory potencies of synthetic racemic ptilocaulin and ten clinical anticancer drugs were determined and compared in 16 different normal and transformed human and murine cell populations. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…For this same line, Ruben et al [22] obtained the average IC 50 value of 0.13 mg/ ml with a synthetic racemic ptilocaulin. The values determined in the present study, however, present a tenfold higher IC 50 array (on HL-60, IC 50 ¼ 5.77 mm corresponds to Hemolysis: ca.…”
mentioning
confidence: 94%
“…For this same line, Ruben et al [22] obtained the average IC 50 value of 0.13 mg/ ml with a synthetic racemic ptilocaulin. The values determined in the present study, however, present a tenfold higher IC 50 array (on HL-60, IC 50 ¼ 5.77 mm corresponds to Hemolysis: ca.…”
mentioning
confidence: 94%
“…Ptilomycalin A displays significant activity against a series of cancer cell lines and DNA polymerase activity of the reverse transcriptase of human immunedeficiency virus type 1 . The tricyclic guanidine ptilocaulin and crambescin A is reported to have a broad spectrum antimicrobial activity in vitro as well as in vivo activity against L1210 murine leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction. -T ricyclic guanidinec ompounds,b earingatricyclic 2-amino-1,3diazaoctahydroacenaphtylene skeleton, like ptilocaulins,mirabilins, and netamines,are restricted to marine sponges of the order Poecilosclerida [1 -11] and can be grouped on the basis of their degree of oxidation and C¼Cb ond position with pyrimidine, D 7, 8 -, D 8,8a -, D 8a,8b -unsaturated, or saturated heterocycles.M any of these alkaloids were reported to possess noteworthy biological activities, i.e.,c ytotoxic [1] [4] [8] [9] [12], antibacterial [1] [7], antifungal [3], antimalarial [3] [11],a nd antiprotozoal activities [3].…”
mentioning
confidence: 99%
“…No correlation was observed between these three Hatoms and HÀC 8 . Thec ytotoxic activity of a synthetic racemic ptilocaulin was studied by Rubent et al [12]inorder to evaluate its in vitro activitiesa gainstv arious cell lines.M oreover, the authors have shown that ptilocaulin was toxic at 50 and 25 mg kg À 1 in an in vivo L1210 tumor model and was ineffective at lower concentrations (T/C 100 -112%).…”
mentioning
confidence: 99%